A call admission control scheme on the uplink of D2D communications underlaying cellular networks. Issue 4 (1st October 2016) - Li, Xujie; Zhang, HongLang; Zhang, Wenna; Yan, Feng
Abstract: In device-to-device (D2D) communications, call admission control (CAC) scheme is a crucial problem. In D2D communications, the cellular user equipment (CUE) and D2D user equipment (DUE) pairs share the same channel resource. Hence additional interference is introduced. Meanwhile, the interference has an important impact on the system performance. In this paper, a CAC scheme based on interference analysis is proposed. First, the interference is modeled and analyzed in detail. Then based on the interference analysis, a CAC scheme is proposed. Simulation results show that D2D communications with the proposed CAC scheme can effectively improve system performance in terms of new call blocking probability and capacity. This proposed scheme can be applied to the design and optimization of D2D communications.